Le manifestazioni per gli 80 anni dell'Ateneo Fiorentino Eventi e programmi - Rogari, Sandro (Firenze University Press, 2005)
This work was commissioned by the Organising Committee for the Eighty Years of the University of Florence. The volume collects the programs of all the events organised during the academic year 2003-2004. For each category of events - honorary degrees, conferences, other events and the awarding of the Salomone d'oro - the programs are shown, followed by a brief summary of the event.